SQL Injection and Cross Site Scripting Prevention using OWASP ModSecurity Web Application Firewall - - Robinson; Memen Akbar; Muhammad Arif Fadhly Ridha (JOIV : International Journal on Informatics Visualization, 2018)
Web Application or website are widely used to provide functionality that allows companies to build and maintain relationships with their customers. The Information stored by web applications is often confidential and, if obtained by malicious attackers. Its exposure could result in substantial losses for both consumers and companies. SQL Injection and Cross Site Scripting are attacks that aiming web application database vulnerabilities. Its can allow malicious attackers to manipulate web server database that can cause various data lost, information thieving, and inconsistent of data. Therefore, this research propose the Open Web Application Security Project (OWASP) ModSecurity Core Rule Set which can help administrator securing the web servers. OWASP operate by blocking IP Address which try to breaking the security rule, monitoring network traffic and preventing suspicious network requesting from outside.